A hybrid flow shop model for an ice cream production scheduling problem - Imma Ribas Vila; Ramon Companys Pascual (Journal of Industrial Engineering and Management (JIEM), 2009)
In this paper we address the scheduling problem that comes from an ice cream manufacturing company. This production system can be modelled as a three stage nowait hybrid flow shop with batch dependent setup costs. To contribute reducing the gap between theory and practice we have considered the real constraints and the criteria used by planners. The problem considered has been formulated as a mixed integer programming. Further, two competitive heuristic procedures have been developed and one of them will be proposed to schedule in the ice cream factory.
Keywords: 650; scheduling; hybrid flow shop; mathematical programming; heuristics